2015
DOI: 10.3399/bjgp15x687373
|View full text |Cite
|
Sign up to set email alerts
|

GPs’ perspectives on secondary cardiovascular prevention in older age: a focus group study in the Netherlands

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
3
12
0
Order By: Relevance
“…However, in line with previous work [48], our interviews suggest that few GPs use a shared decision making approach and many refer to challenges associated with older patient involvement, including: third party involvement, a perception that older patients prefer a paternalistic relationship with their GP, and cognitive impairment. This is somewhat in contrast with a focus group study on secondary CVD prevention in which the majority of GPs mentioned using shared decision making as a way to deal with uncertainties around the management of older people [43]. The majority of the GPs in this study were highly skilled GPs (e.g.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, in line with previous work [48], our interviews suggest that few GPs use a shared decision making approach and many refer to challenges associated with older patient involvement, including: third party involvement, a perception that older patients prefer a paternalistic relationship with their GP, and cognitive impairment. This is somewhat in contrast with a focus group study on secondary CVD prevention in which the majority of GPs mentioned using shared decision making as a way to deal with uncertainties around the management of older people [43]. The majority of the GPs in this study were highly skilled GPs (e.g.…”
Section: Discussionmentioning
confidence: 58%
“…A qualitative focus group study of secondary CVD prevention in older people found similar dilemmas and uncertainties about the potential benefits and harms of secondary cardiovascular prevention, with management often based on frailty rather than chronological age [43]. …”
Section: Discussionmentioning
confidence: 99%
“… 21 This reluctance is, among other factors, induced by GPs’ anticipated regret, which has been previously described as a motivator to start or continue preventive treatment. 17 22 The fear of ‘causing’ a stroke by deprescribing AHM is unsupported by clinical evidence but might be instigated by results from trials like the SPRINT trial that support intensive BP lowering, 6 even though multimorbid older people are potentially under-represented in this trial and the generalisability of these results is uncertain. 8 Also for deprescribing shared decision-making is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Even where evidence suggests benefits of preventive medication for older people, as is the case for secondary prevention, the evidence becomes uncertain in the context of complex interactions between multiple conditions and medications, the generally higher risk of side effects, declining health and limited life expectancy as trial data is not available for these groups 18 19. It is therefore not a surprise that general practitioners (GPs) are uncertain about CVD prevention in older age, and there is evidence of overtreatment and undertreatment of CVD risk in this group 20–22. This is why an SDM approach to CVD management has now been universally advocated, in particular for those who are older, frail or have comorbidities 23–26…”
Section: Introductionmentioning
confidence: 99%